Digitalisasi Zakat dan Transformasi Kesejahteraan Sosial Islam: Model Tata Kelola Berbasis Maqasid al-Shariah di Arab Saudi - Jaeni Miftah Fatunijar; Fakri Jamil; Soeharjoto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Digital transformation brings changes to the governance of Islamic social finance, particularly in the management of zakat. Aim of this study is to analyze the implementation of zakat management digitalization in Saudi Arabia through the Zakat, Tax and Customs Authority (ZATCA) and its impact on the efficiency, transparency, accountability, and participation of muzakki. The research was conducted using a descriptive qualitative approach based on literature studies with secondary data analysis from scientific literature, institutional reports, and official policies related to the digitalization of zakat. Research results show that the digitalization of zakat in Saudi Arabia has integrated the processes of collection, calculation, payment, and distribution of zakat in real-time through an information technology-based system. Integration with the Social Security Agency strengthens the accuracy of distribution targets to the eight categories of beneficiaries, while also enhancing transparency and accountability based on digital data. Digitalization has proven to increase the participation of muzakki through ease of access, legal certainty, and enhanced trust in zakat management institutions. However, the implementation of this system still faces challenges such as the digital literacy gap, data security, and the need for regulatory harmonization between Sharia principles and technological advancements. Overall, the digitalization of zakat in Saudi Arabia represents a model of smart zakat governance that is not only administratively efficient but also aligned with the values of justice, trust, and the welfare of the community in the modern Islamic economy.